Perkawinan Sepersusuan Menurut Hadis Dan Ditinjau Dari Hukum Positif Indonesia - Nurmahmudah (LPPM IAIN Kediri, 2022)
Marriage is one of the human needs in fulfilling their spiritual and biological needs but is regulated by law so as not to harm others, and provide great benefits to society. Islam regulates these issues through laws. Hadith is one of the sources of dalil naqli for Islamic law. Therefore, in this explaining the marriage of brothers and sisters, start from takhrij of the hadith which is selected from the method of the narrator or rawi, then from the lafadz, and finally select the hadith about the relationship between brothers and sisters through the classification of the hadith by selecting the sahih hadith. The second step is to corroborate with the Qur'an and ulama interpretations, qiyas and ijtihad. The last step is to look at this law from the perspective of Indonesian positive law, No. 1 of 1974 concerning marriage and also strengthened by Presidential Instruction No. 1 of 1991 concerning the Dissemination of the Compilation of Islamic Law concerning marriage, which then specifies marriage of brothers, sisters and cousins. The criterias is in the hadith are the same as those in Indonesian positive law, even more detailed. This means that Indonesian law does not contradict Islamic law.